Fiber orientation angle effects in machining of unidirectional CFRP laminated composites. (October 2015) - Madhavan, V.; Lipczynski, G.; Lane, B.; Whitenton, E.
Abstract: Experiments were carried out at the National Institute of Standards and Technology, in collaboration with The Boeing Company, to obtain force and temperature data as a function of feed, speed, and fiber orientation angle (FOA), for validation of finite element simulations of composite machining. The outer diameter portions of disks of unidirectional carbon fiber reinforced plastic (CFRP) laminates were cut orthogonally. Tabs were machined into the outer diameter (OD) to cause cutting to begin at a FOA of 0° and end at a FOA of 90°. Cutting forces were measured using a dynamometer and the chip morphology was recorded using a high speed camera. It was observed that the variation of cutting force with FOA depended on the feed. For large feed, the cutting force increases with FOA until an angle of 90°, whereas for low feed the cutting force decreases beyond 65°. The chip morphology also changes with FOA and feed. Significant tool flank wear is noted even in these short duration experiments, which causes the thrust and cutting forces to increase significantly for FOA from 0° to 60°. For 65°–80° FOA, force signals change cyclically. A small spike in the cutting force seems to be correlated with fibers being pulled out in clumps, and is followed by lower forces in subsequent revolutions while the pitted surface is machined.